PP6 Disruption Synergizes with Oncogenic Ras to Promote JNK-dependent Tumor Growth and Invasion - Ma, Xianjue (Cell Rep, 2017)
RAS genes are frequently mutated in cancers, yet an effective treatment has not been developed. This is partly due to an incomplete understanding of signaling within Ras-related tumors. To address this, we performed a genetic screen in Drosophila, aiming to find mutations that cooperate with oncogenic Ras (Ras(V12)) to induce tumor overgrowth and invasion. We identified fiery mountain (fmt), a regulatory subunit of the protein phosphatase 6 (PP6) complex, as a tumor suppressor that synergizes with Ras(V12) to drive JNK-dependent tumor growth and invasiveness. We show that Fmt negatively regulates JNK upstream of dTAK1. We further demonstrate that disruption of PpV, the catalytic subunit of PP6, mimics fmt loss of function induced tumorigenesis. Finally, Fmt synergizes with PpV to inhibit JNK-dependent tumor progression. Our data here further highlight the power of Drosophila as a model system to unravel molecular mechanisms that may be relevant to human cancer biology.